Resuscitative endovascular balloon occlusion of the aorta: an option for noncompressible torso hemorrhage? - Kulla, Martin; Popp, Erik; Knapp, Jürgen (Current opinion in anaesthesiology, 2019)
Purpose of reviewHemorrhage is the major cause of early death in severely injured patients. In civilian emergency medical services, the majority of life-threatening bleedings are found in noncompressible body regions (e.g. abdomen and pelvis). Resuscitative endovascular balloon occlusion of the aort
Gesehen am 24.03.2020